Investigating the prevalence of primary thyroid dysfunction in obese and overweight individuals: Tehran thyroid study - Mahdi Mahdavi; Atieh Amouzegar; Ladan Mehran; Elham Madreseh; Maryam Tohidi; Fereidoun Azizi (BMC Endocrine Disorders, 2021)
Abstract Background Due to the increasing worldwide prevalence of obesity, it is essential to determine the prevalence of obesity-related thyroid dysfunctions. The purpose of this study was to investigate the prevalence of thyroid dysfunctions, namely hypothyroidism and hyperthyroidism, and their association with BMI among adult Iranian overweight and obese individuals. Method This cross-sectional study was carried out within the framework of the Tehran Thyroid Study (TTS); 5353 participants (57.5% female) entered our study. Anthropometric measurements were performed. Serum levels of thyroid-stimulating hormone (TSH), free thyroxine (FT4), and thyroid peroxidase antibody (TPOAb) were assayed. We categorized individuals into 3 BMI groups (normal-weight, overweight and obese), then calculated prevalence rate, odds ratio (OR), and 95% confidence interval (CI) for outcomes in overweight and obese groups. The normal-weight group was used as the control group. Results We found a higher prevalence of hypothyroidism (11.6% vs 8.2% Total, 4.0% vs 1.1% overt and 7.6% vs 7.1% subclinical, P < 0.001) and TPOAb positivity (17.3% vs 11.6%, P < 0.001) in obese participants compared with normal-weight participants. Hyperthyroidism’s overall prevalence was 4.2, 5.7, and 4.9% in obese, overweight, and normal-weight groups, respectively. Obesity was associated with higher odds of overt hypothyroidism (OR: 2.0, 95% CI: 1.15–3.49, P < 0.05) and TPOAb positivity (OR: 1.29, 95% CI: 1.04–1.60, P < 0.05) after adjusting for confounding variables. In contrast, no association was observed between the overweight group and the odds of hypothyroidism and TPOAb positivity in the adjusted results. Conclusions Obesity was associated with an increased risk of overt hypothyroidism and TPOAb positivity.